THE LOSS OF PHENOTYPIC TRAITS BY DIFFERENTIATED CELLS : III. The Reversible Behavior of Chondrocytes in Primary Cultures - Abbott, Joan (The Rockefeller University Press, 1966)
Observations were made on the behavior of chondrocytes grown under various conditions in vitro. The chondrocytes in 10-day embryonic chick vertebrae were grown as cultures of intact vertebrae, as pellets of chondrocytes liberated from their matrix, and as monodispersed cells plated out on plasma clots. Cartilage matrix was stained metachromatically with toluidine blue. Radioautographs were made of incorporated H(3)-thymidine, H(3)-proline, and S(35)-sulfate to determine the extent of DNA synthesis, collagen synthesis, and chondroitin sulfate synthesis, respectively. Chondrocytes in intact vertebrae or in pellets are rounded and actively synthesizing chondroitin sulfate and collagen. There is little DNA synthesis by cells in either vertebrae or pellets. Chondrocytes grown as monodisperse cells rapidly cease synthesizing cytologically detectable chondroitin sulfate and are induced to synthesize DNA and divide. There is a change in the shape of these chondrocytes from a rounded to a more stellate condition which accompanies the shift in metabolic activity. Conversely, when the cells attain a certain cell density, they reacquire a rounded shape, cease dividing, and again synthesize chondroitin sulfate. Clusters of chondrocytes synthesize more chondroitin sulfate than isolated chondrocytes. It is concluded that most chondrocytes synthesizing chondroitin sulfate do not concurrently synthesize DNA. Interaction between associated chondrocytes is important in inducing and maintaining chondroitin sulfate synthesis in genetically determined chondrocytes. Failure of interaction between chondrocytes leads to DNA synthesis and cell multiplication.